Exploring Mental Health Prevalence Among Multiethnic High School Adolescents in West Kalimantan - Hendrik Hendrik; Yenni Rizal; Hendra Sulistiawan; Melina Lestari; Ely Trisnowati; Uray Herlina; Hema Fitria; Dada Suhaida (STAI Hubbulwathan Duri, 2025)
Mental health among adolescents is a growing concern, particularly in culturally diverse regions. This study investigates the mental health status of multiethnic adolescents at State Senior High School 1 Sungai Kakap, West Kalimantan, Indonesia, focusing on six major ethnic groups: Malay, Dayak, Chinese, Bugis, Madurese, and Javanese. A quantitative, descriptive research design was employed. Data were collected through a mental health assessment and analyzed using percentage calculations. Each participant’s score was categorized, and the proportion of individuals in each category was computed by dividing the frequency (ni) by the total number of participants (n), then multiplied by 100. Findings indicate that, overall, the mental health of multiethnic adolescents falls within the